PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN LITERASI EKONOMI TERHADAP PERILAKU KONSUMTIF SISWA DI SMK NEGERI 1 BITUNG - Mamentu, Meike Drita; Winokan, Amsje Norma; Tatinting, Prayzy Gracia (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to determine how to determine the influence of parents' socio-economic status and economic literacy together on students' consumer behavior at SMK Negeri 1 Bitung. The research method used is a survey method, which is sourced from data and information mainly obtained from respondents as research samples using questionnaires or questionnaires as data collection instruments. The population in this study were 96 students of class XI OTKP at SMK N 1 Bitung. The sampling technique used was random sampling with a level of 5% so that a sample of 77 students was obtained. The results of the study showed that the variable of parents' socio-economic status had a positive or significant influence on students' consumer behavior at SMK Negeri 1 Bitung, the variable of parents' socio-economic status, the variable of economic literacy together had a positive or significant influence on students' consumer behavior at SMK Negeri 1 Bitung. Keywords: Parents' Socio-Economic Status, Economic Literacy, Consumptive Behavior